Kustības jēdziena apguve vispārizglītojošās skolas fizikā” - Legzdiņa, Anita (Latvijas Universitāte, 2013)
The diploma paper has been worked out at the Faculty of Pedagogy, Psychology and Arts, University of Latvia in cooperation with the Faculty of Physics and Mathematics. The work consists of 56 pages in total, including Introduction (2 pages), two Parts (16 and 18 pages), Conclusion (1pages), as well as List of used information (12 sources), and Enclosure (9 items). There are 8 drawings and 12 charts in the text. Acquisition of Motion Concept in Comprehensive School. The aim of the diploma paper is to work out topical content and assessment methods of its realization for teacher of Physics in modern secondary school. In the process of work available teaching aids have been studied in the light of their content and methodology, a project of practical realization of the theme within the chosen program of the subject has been built up, the efficiency of elaboration has been tested in teaching practice, as well as conclusions have been made, and proposals for the further development and completion have been prepared. The main result of the work is the complex project of planning of the chosen theme in Physics, topical content and methodical security of school lessons have been worked out, as well as schoolchildren achievement assessment methods. Key words: topical content, methods of content acquisition, schoolchildren achievement assessment methods.
Acquisition of the movement concept in the general physics course in school
Keywords: Pedagoģija